The effect of load distribution towards the line following performance of two wheel driven mobile robot - Ahmad Sohan, Muhammad Hafiz (2014)
In a mobile robot competition, it is often that the challenge includes carrying a load in the form of an object or sometime carrying another robot. The line following performance of the mobile robot might be affected by the way the load is distributed on top of them. To ensure the performance of line following, the mobile robot must be designed with these varying load distributions under consideration. Therefore, this thesis is designed to take the first step which is identifying the effect of load distribution towards the performance of line following. A two wheel driven mobile robot with a differential drive steering is developed with a platform to compensate different types of load distribution. A series of experiments is carried out to observe the effect of each type of load distribution towards the line following performance of the robot while completing the line following tasks. The performance of line following task is measured based on the time taken to complete a task and the frequency of line following sensors straying off the line. Data analysis is performed on results of the experiments to conclude the effect of each type of load distribution towards the line following performance. From the obtained result it can be concluded that the load distribution undoubtedly has effects towards the line following performance. The best position for load placement is at the centre of the robot polygon support which is represented by position 5 in the experiments. The outcome of this thesis research should benefits the development of load carrying mobile robot for competition and industrial automated guided vehicle which are navigated using the line following method.